2015
DOI: 10.3998/jmmh.10381607.0009.101
|View full text |Cite
|
Sign up to set email alerts
|

African Refugee Youths’ Stories of Surviving Trauma and Transition in U.S. Public Schools

Abstract: The educational landscape for the United States has continued to shift with the arrival of African Muslim youth with refugee status. This phenomenological study examines the lived experiences of college-aged refugees (ages 18-22) attending various public (community and 4-year) colleges in the western United States. The participants' (N=12) narratives address the carryover effects of trauma including the challenges of racism, discrimination, and Islamophobia. This discussion further explores the ways in which A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A study in Norway demonstrated a positive effect of cultural competence and social support on refugee youth’s abilities to handle discrimination, even with high levels of overall mental distress (Oppedal & Idsoe, 2015). In the US, African Muslim adolescents were interviewed in a qualitative study about their adjustment to public schools; a prominent theme of their narratives focused on Islamophobia, discrimination, and racism (Haffejee, 2015); Somali refugee adolescents also experienced discrimination in the US (Ellis et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Norway demonstrated a positive effect of cultural competence and social support on refugee youth’s abilities to handle discrimination, even with high levels of overall mental distress (Oppedal & Idsoe, 2015). In the US, African Muslim adolescents were interviewed in a qualitative study about their adjustment to public schools; a prominent theme of their narratives focused on Islamophobia, discrimination, and racism (Haffejee, 2015); Somali refugee adolescents also experienced discrimination in the US (Ellis et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It was clear that the urban school and its context, filled with danger and crimes, would not help to accumulate the kind of cultural capital that enabled post-secondary education. While some children may make it to college against all odds, most will probably not, as documented in other studies (Gans, 2009;Haffejee, 2015;McWilliams & Bonet, 2016). Similarly, the ESL programme may have subtracted the multilingual cultural capital that these children brought with them and also the academic literacy that they needed to succeed in the mainstream classrooms.…”
Section: Discussion S and Con Clus I On Smentioning
confidence: 97%
“…At the macro level, public funding cuts had led to a lack of support services, resulting in refugee students being left to sink or swim in ‘schools in crisis’ (McWilliams & Bonet, , p. 164). At the micro level, school curriculum and spaces have been unwelcoming to refugee (and immigrant) students with different linguistic, cultural, ethnic, or religious backgrounds (Haffejee, ). As Gitlin, Buendia, Crosland, & Doumnia () documented, these students were marginalised in school programmes; and this marginalisation was ‘motivated by employment issues, the concerns of local businesses, fear of potential violence, and the wish to maintain an academic advantage’ (p. 91) among teachers, mainstream students and the local white community surrounding the school.…”
Section: Refugee Children's School Transition In the Transnational Somentioning
confidence: 99%
“… Abdi, 2015 , Al-Jazeera, 2019 , Asanov et al, 2021 , Bal, 2014 , Beiser et al, 2015 , Beiser and Hou, 2016 , Beni Yonis et al, 2020 , Betancourt et al, 2012 , Bolton and Betancourt, 2004 , Bonet, 2018 , Bozkurt et al, 2020 , Brooks et al, 2020 , Bronstein et al, 2013 , Çelebi et al, 2017 , Çeri and Nasiroğlu, 2018 , Chang-Bacon, 2021 , Chen and Schweitzer, 2019 , Christensen et al, 2020 , Clukay et al, 2019 , Correa-Velez et al, 2010 , COVID-19 and children's rights., 2020 , Department of Homeland Security., 2017 , Diaków and Goforth, 2021 , Dorner et al, 2017 , El Baba and Colucci, 2018 , Endale et al, 2020 , Eruyar et al, 2018 , Farzana et al, 2020 , Fazel et al, 2012 , Fazel and Betancourt, 2018 , Federal Register, 2017 , Guglielmi et al, 2020 , Guo et al, 2021 , Guterman et al, 2010 , Haffejee, 2015 , Henley and Robinson, 2011 , Hynie et al, 2013 , Jabbar and Zaza, 2014 , Kliewer et al, 2020 , Kunst et al, 2012 , Migration Policy Institue, 2019 , New York Times, 2021 , Nunn et al, 2017 , Primdahl et al, 2020 , Prodip, 2017 , Refugee Processing Center, 2021 , Saleebey, 1996 , Scharpf et al, 2020 , Shaw et al, 2020 , Trump White House Archives, 2017 , United Nations High Commissioner for Refugees & Plan International, 2012 , United Nations High Commissioner for Refugees, 1954 , United Nations High Commissioner for Refugees, 2015 , United Nations High Commissioner for Refugees...…”
Section: Uncited Referencesmentioning
confidence: 99%